A MULTIMODAL ANALYSIS OF THE REPRESENTATION OF THE EGYPTIAN PRESIDENT IN AL AHRAM EGYPTIAN NEWSPAPER IN 2012 - Al Sawi, Islam M. (European Scientific Journal, ESJ, 2015)
Previous Critical Discourse Analysis (CDA) studies on Egyptian newspapers have revealed ideological bias. However, these studies focused only on the text. Since newspapers integrate texts and images to make meaning, an analysis of the textual and the visual components is necessary to better understand the meaning. This study focuses on the analysis of the textual and visual representation of the Muslim Brotherhood (MB) President Muhammad Morsi during the first week of his office in 2012 on the front page of Al Ahram newspaper. The analysis is based on the linguistic tools suggested by Fowler (1991), and the visual tools suggested by Kress and van Leeuwen (2006). The textual analysis revealed that Al Ahram positively represents the MB president as a powerful leader performing material action verbs with modality of absolute certainty. The visual analysis also showed the bias of Al Ahram towards the MB president by representing him in a higher position than the masses and as the new information. The multimodal analysis agrees with previous CDA research on newspapers in showing the newspapers’ bias, and contradicts Pasha’s (2011) results by showing the positive representation of the MB president during his office.